Identification of patient endotypes and adalimumab treatment responders in axial spondyloarthritis using blood-derived extracellular matrix biomarkers - Anne Gitte Loft; Inge Juul Sørensen; Mikkel Østergaard; Susanne J Pedersen; Morten Asser Karsdal; Ole Rintek Madsen; Anne-C Bay-Jensen; Peder Frederiksen; Signe Holm Nielsen; Helena Port; Frederik Christiansen; Sengul Seven (RMD Open)
Objective To explore the potential of a panel of ECM remodelling markers as endotyping tools for axial spondyloarthritis (axSpA) by separating patients into subtypes and investigate how they differ among each other in disease activity scores and response to treatment with adalimumab.Methods In three axSpA studies, a panel of 14 blood-based ECM biomarkers related to formation of collagen (PRO-C2, PRO-C3, PRO-C6), degradation of collagen by metalloproteinases (C1M, C2M, T2CM, C3M, C4M, C6M, C10C), matrix metalloproteinase (MMP)-degraded prolargin (PROM), MMP-degraded and citrullinated vimentin (VICM), basement membrane turnover (PRO-C4) and neutrophil activity (CPa9-HNE) were assessed to enable patient clustering (endotyping). MASH (n=41) was a cross-sectional study, while Adalimumab in Axial Spondyloarthritis study (ASIM,n=45) and Danish Multicenter Study of Adalimumab in Spondyloarthritis (DANISH, n=49) were randomised, double-blind placebo-controlled trials of adalimumab versus placebo every other week for 6 or 12 weeks, respectively, followed by active treatment. Biomarker data were log-transformed, standardised by mean centering and scaled by the SD prior to principal component analysis and K-means clustering.Results Based on all three studies, we identified two orthogonal dimensions reflecting: (1) inflammation and neutrophil activity (driven by C1M and CPa9-HNE) and (2) collagen turnover (driven by PRO-C2). Three endotypes were identified: high inflammation endotype (Endotype1), low inflammation endotype (Endotype 2) and high collagen turnover endotype (Endotype3). Endotype1 showed higher disease activity (Ankylosing Spondylitis Disease Activity Score (ASDAS)) at baseline compared with Endotype2 and Endotype3 and higher percentage of patients responding to adalimumab based on ASDAS clinical improvement at week 24. Endotype3 showed higher percentage of patients with 50% improvement in Bath Ankylosing Spondylitis Disease Activity Index response at week 24 compared with Endotype2.Conclusion These endotypes differ in their tissue remodelling profile and may in the future have utility for patient stratification and treatment tailoring.